Efektivitas Model RMS (Reading, Mind Mapping and Sharing) Terhadap Concept Mapping Skill Peserta Didik - Diani, Rahma; Julia, Orin Neta; Rahayu, Murih (Indonesian Journal of Science and Mathematics Education, 2018)
Abstract: The purpose of this study is to determine the effectiveness of physics learning by using the model of learning RMS (Reading, Mind Mapping and Sharing)to the comcept mapping skill of learners. This research is a kind of quasy experiment research. Sampling technique is done with porposive sampling technique. To measure and know the concept mapping skill with assessinh 4 aspect of the concept mapping skill. The result of analysis stated that there is difference of at a time when learners start making mind mapping in the first meeting, second meeting and the third meeting. This is evidenced from the acquisition of percentage of 49,30% at then first meeting, 74,58% at second meeting, and 90,13% at the third meeting which mean an increase in the ability create a mind map with the use of RMS (Reading, Mind Mapping and Sharing model. Then it can be concluded that, the study of physics with the RMS (Reading, Mind Mapping and Sharing) model more Effective against concept mapping skill.  Abstrak: Tujuan penelitian ini adalah untuk mengetahui efektivitas pembelajaran fisika dengan menggunakan  model pembelajaran RMS (Reading, Mind Mapping and Sharing) terhadap concept mapping skill peserta didik. Penelitian ini merupakan jenis penelitian quasy experimen.Teknik pengambilan sampel dilakukan dengan tehnik purposive sampling. Untuk mengukur dan mengetahui kemampuan konsep mapping peserta didik dengan menilai 4 aspek dalam concept mapping. Hasil analisis menyatakan bahwa terdapat perbedaan pada saat peserta didik memulai pembuatan mind mapping di pertemuan pertama, pertemuan kedua dan pertemuan ketiga. Hal ini dibuktikan dari perolehan nilai presentase sebesar 49,30% pada pertemuan pertama, 74,58% pada pertemuan kedua dan 90,13% pada pertemuan ketiga yang berarti adanya peningkatan pada kemampuan membuat mind map dengan pengguanaan model RMS (Reading, Mind Mapping and Sharing). Maka dapat disimpulkan bahwa, pembelajaran fisika dengan model RMS (Reading, Mind Mapping and Sharing) lebih efektif terhadap concept mapping skill peserta didik.